Progestogens in Menopausal Hormone Therapy: A Double-Edged Sword - Ylikorkala, Olavi; Joensuu, Johanna M.; Siitonen, Heli; Mikkola, Tomi S. (Seminars in Reproductive Medicine, 2025)
Progestogens (norethisterone acetate, medroxyprogesterone acetate, dydrogesterone, micronized progesterone, levonorgestrel, drospirenone, and trimegestone) added to estrogen for endometrial protection are reviewed. They can be given orally or vaginally, norethisterone acetate can also be given transdermally, and levonorgestrel can be given through the intrauterine route. Sequential use of progestogens protects the endometrium if exposure lasts for at least 12 days/month; longer intervals are not safe. Continuous use of progestogens, whether oral, transdermal, or intrauterine, provides the most effective protection. Progestogen addition is accompanied with significant elevations in breast cancer risk, the largest drawback of progestogen use, and dydrogesterone, micronized progesterone, and a levonorgestrel intrauterine device may be safest in this regard. Progestogens also double deep vein thrombosis risk and diminish the positive effect of estrogen on colorectal cancer and vascular health. Recent data imply a neutral effect of progestogens in combination with estrogen on Alzheimer's disease risk, but the risk of vascular dementia is decreased. In conclusion, progestogens are a double-edged sword, effectively protecting the endometrium but causing several side effects and reducing many estrogen-induced benefits. With modern endometrial diagnostic tools, the safety of low-dose unopposed estrogen regimens should be assessed in a prospective controlled trial in women with an intact uterus.
Keywords: endometrium protection; androgen; breast cancer